Gene Therapy for Acute Respiratory Distress Syndrome - Liu, Jing; Dean, David A. (Frontiers in Physiology, 2022)
Acute respiratory distress syndrome (ARDS) is a devastating clinical syndrome that leads to acute respiratory failure and accounts for over 70,000 deaths per year in the United States alone, even prior to the COVID-19 pandemic. While its molecular details have been teased apart and its pathophysiology largely established over the past 30 years, relatively few pharmacological advances in treatment have been made based on this knowledge. Indeed, mortality remains very close to what it was 30 years ago. As an alternative to traditional pharmacological approaches, gene therapy offers a highly controlled and targeted strategy to treat the disease at the molecular level. Although there is no single gene or combination of genes responsible for ARDS, there are a number of genes that can be targeted for upregulation or downregulation that could alleviate many of the symptoms and address the underlying mechanisms of this syndrome. This review will focus on the pathophysiology of ARDS and how gene therapy has been used for prevention and treatment. Strategies for gene delivery to the lung, such as barriers encountered during gene transfer, specific classes of genes that have been targeted, and the outcomes of these approaches on ARDS pathogenesis and resolution will be discussed.